A Novel Electrochemical Aptamer Biosensor Based on DNAzyme Decorated Au@Ag Core-Shell Nanoparticles for Hg2+ Determination - Zhao,Yanling (2018)
As a kind of important water pollutant, heavy metal ions have a detrimental effect on the health of human. In this study, Au@Ag core-shell nanoparticles were synthesized by simple reduction of Ag + around Au nanoparticles and functionalized by DNAzyme. Based on thymine-Hg2+-thymine binding mode, a sensitive aptamer biosensor was constructed by utilizing functionalized Au@Ag core-shell nanoparticles as labels, and the sensitivity was enhanced by DNAzyme due to the catalysis toward H2O2. Under optimal conditions, square wave voltammetry was carried out to measure the current derived from Au@Ag nanoparticles labels. The current response of biosensor increased with the increasing of Hg2+ concentration, which presented linear relation in the range of 0.002-20 μg L -1 with limit of detection of 0.006 μg L -1. Meanwhile, the electrochemical biosensor showed superior reversibility, stability, repeatability, and selectivity.